DESCRIPTION OF AGE, CENTRAL CORNEAL THICKNESS AND INTRAOCULAR PRESSURE IN PATIENTS AT DEPARTMENT OF OPHTHALMOLOGY PHC HOSPITAL SURABAYA - Ivaldo Hadi Ardhana; Titiek Ernawati; Gladdy Lysias Waworuntu (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2023)
Background: Eyes are one of the most important sense organs in human life. Eyes can help humans in activities and get information visually. Disorders of the eye will hinder and make it difficult for humans to carry out daily activities and reduce the quality of life. The cornea is one of the most important parts of the eye. Central Corneal Thickness (CCT) is the middle part of the cornea. CCT examination is a routine examination that must be carried out, but there are still many who have not carried out routine CCT examinations. Patients with thick CCTs may cause the IOP readings to appear higher than the actual condition, and conversely, patients with thinner CCTs may give the interpretations the impressions that they are lower than the actual condition. Data related to CCT and IOP in Indonesia is still lacking, especially in Surabaya, so a search for research on age, CCT and IOP needs to be done.Objective: The purpose of this study was to describe data on age, CCT and IOP in patients aged 20 to 70 years in the outpatient polyclinic of Ophthalmology, PHC Hospital Surabaya.Methods: This study used a cross-sectional research design. The sampling method used is total sampling.Result: In this study, CCT was examined using a Canon TX-20P measuring instrument and examined on both eyes. The average CCT examination results in the 20-30 age group was 537.67 ± 28.16 μm and the 31-40 age group 544.89 ± 29.28 μm. In the age group 20-30 and 31-40 years, the CCT increased by 7.22 μm, however in the 41-50 age group, the average CCT was 540.09 ± 30.44 μm, which showed a decrease of 4.80 μm compared to 31-40 age group. In the 51-60 age group, the results were 553.35 ± 28.60 μm which showed an increase in CCT compared to the 41-50 age group and the 61-70 age group got the results of 550.35 ± 30.47 μm showing a decrease of 3.00 m compared to the 51-60 age group. IOP in the 20-30 age group obtained results of 16.25 ± 2.93 mmHg, this value is lower than the 31-40 age group. In the age group 31-70 years, the results of IOP decreased over time.Conclusion: Descriptive data obtained regarding age, CCT and IOP that can be used as baseline data or comparison in eye examinations.Keyword: Central Corneal Thickness, Intraocular Pressure, Eyes, Age, Cornea.